1978
DOI: 10.3109/00365527809181767
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Hyperoxaluria: Dependence on Small Intestinal Resection, Colectomy, and Steatorrhoea in Chronic Inflammatory Bowel Disease

Abstract: The importance of intestinal resection, exclusion of the colon, and steatorrhoea for secondary hyperoxaluria was studied in 81 patients with Crohn's disease and 12 patients with ileostomy after colectomy for ulcerative colitis during a metabolic regime including a fixed oral supply of fat, calcium, and oxalate. Hyperoxaluria (greater than 48 mg (greater than 0.5 mmol) per 24 h) was present in 21 patients with Crohn's disease. All but one half or more of the colon preserved. Renal oxalate excretion was related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 18 publications
2
39
0
2
Order By: Relevance
“…Increased dietary oxalate absorption has been implicated in the etiology of calcium oxalate nephrolithiasis both in the presence and apparent absence of intestinal disease (1)(2)(3)(4)(5)(6). Until recently most investigators had concluded that oxalate was absorbed by a passive, noncarrier-mediated pathway and that increased absorption resulted from increased passive permeability and/or increased solubility of oxalate (2)(3)(4)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased dietary oxalate absorption has been implicated in the etiology of calcium oxalate nephrolithiasis both in the presence and apparent absence of intestinal disease (1)(2)(3)(4)(5)(6). Until recently most investigators had concluded that oxalate was absorbed by a passive, noncarrier-mediated pathway and that increased absorption resulted from increased passive permeability and/or increased solubility of oxalate (2)(3)(4)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently most investigators had concluded that oxalate was absorbed by a passive, noncarrier-mediated pathway and that increased absorption resulted from increased passive permeability and/or increased solubility of oxalate (2)(3)(4)(7)(8)(9)(10)(11)(12)(13)(14). Hatch et al (15), SITS),' which suggests an anion exchange process on the brush border.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, an accumulation of oxalic acid can result in a number of pathological conditions, including hyperoxaluria, calcium oxalate nephrolithiasis, cardiomyopathy, and cardiac conductance disorders (24,39,51). In addition, several pathological conditions, including Crohn's disease, steatorrhea, and cystic fibrosis, or medical procedures such as jejunoilean bypass surgery are associated with enteric hyperoxaluria due to enhanced oxalic acid absorption in the colon (12,22,32). The importance of the colonic segment in regulating oxalic acid homeostasis has focused attention on the possible role oxalate-degrading colonic anaerobic bacteria may have in oxalate-related diseases.…”
mentioning
confidence: 99%
“…Oxalate precursors incriminated in toxic or drug-induced AON include acute poisoning by ethylene glycol (8) and ascorbic acid (21), respectively. Enteric hyperoxaluria has been described in various malabsorptive intestinal diseases, like jejuno-ileal bypass (17,22), short bowel syndrome (23,24), and chronic inflammatory bowel disease (25)(26)(27). Recently, short series have emphasized the risk of AON after modern bariatric surgery with Roux-en-Y gastric bypass (5,9).…”
Section: Discussionmentioning
confidence: 99%